Negotiating for fertilizer - Brett, Jeanne M. (SAGE knowledge. Cases., 2016)
One Acre Fund (OAF) was founded by Andrew Youn in 2005 for the purpose of helping to solve the chronic hunger problem in Africa. The idea is to provide the resources (seed, fertilizer, and education) necessary for African farm families to feed themselves when their land holdings are one acre or less. The business model of OAF is that of a cooperative: OAF buys resources like seeds and fertilizer in bulk at reduced prices and distributes them to small farmers who otherwise could not afford them. This case concerns the negotiation that OAF's manager of external relations and research, Moises Postigo, conducted to buy fertilizer in the last quarter of 2007. The case provides an opportunity for students to analyze a real-world deal-making negotiation.